The Effectiveness of A Gamified Vocabulary learning Media for Thai Junior High School Students - Amy Divanio Arcella; Yusriati; Dewi Kesuma Nst (Universitas Majalengka, 2026)
This study aims to determine the effectiveness of gamification-based learning media in improving vocabulary mastery among junior high school students in Thailand and to examine whether there is a significant difference between students’ vocabulary achievement before and after the implementation of gamification. This research employed a quantitative experimental design using a pre-test and post-test approach. The population of this study consisted of 40 seventh-grade students at Nida Suksasat School, while the sample included 20 students selected for the experimental group. The data were collected through vocabulary tests administered before and after the treatment. The data were analyzed using descriptive statistics, normality testing (Shapiro-Wilk), and paired sample t-test. The results of the study showed that the mean score increased from 53.65 in the pre-test to 78.80 in the post-test. The normality test indicated that the data were normally distributed, with significance values greater than 0.05. Furthermore, the paired sample t-test revealed a significance value of less than 0.05, indicating that there is a statistically significant difference between pre-test and post-test scores. Based on these findings, it can be concluded that gamified vocabulary learning media is effective in improving students’ vocabulary mastery. The use of gamification elements such as points, badges, and leaderboards contributes to increased motivation, engagement, and active participation, resulting in better learning outcomes. Therefore, gamification can be considered an effective and innovative approach to vocabulary learning, especially in EFL contexts like Thailand.